2007
DOI: 10.1542/peds.2007-0257
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clinical Alerts Within an Electronic Health Record on Routine Childhood Immunization in an Urban Pediatric Population

Abstract: An electronic health record-based clinical alert intervention was associated with increases in captured opportunities for vaccination at both sick and well visits and significant improvements in immunization rates at 2 years of age. As electronic health records become more common in medical practice, such systems may transform immunization delivery to children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 37 publications
4
113
3
Order By: Relevance
“…17 More importantly, the use of shot reminders at sick visits through electronic health record systems has already been demonstrated to substantially improve sick-visit shot rates. 18 Previous work has also shown that most parents are agreeable to sick-visit shots if their providers recommend them. 19 In the United States, many providers who support immunization are also reluctant to adopt practices of giving or checking for immunizations at sick visits.…”
Section: Discussionmentioning
confidence: 99%
“…17 More importantly, the use of shot reminders at sick visits through electronic health record systems has already been demonstrated to substantially improve sick-visit shot rates. 18 Previous work has also shown that most parents are agreeable to sick-visit shots if their providers recommend them. 19 In the United States, many providers who support immunization are also reluctant to adopt practices of giving or checking for immunizations at sick visits.…”
Section: Discussionmentioning
confidence: 99%
“…The clinician-focused intervention consisted of 3 components: (1) EHRbased alerts for all routine adolescent vaccinations programmed to appear prominently whenever any patient encounter at an intervention practice was opened within the EHR ( Supplemental Fig 3), 24,25 (2) a 1-hour presentation delivered in person or online to introduce the intervention, provide site-specific data on HPV vaccination rates derived from the EHR, and present evidenced-based information on adolescent vaccine safety, efficacy, and strategies for overcoming barriers to vaccine receipt, 31 and (3) 3 quarterly performance feedback reports generated from EHR data and delivered by a research assistant including individual, practice, and network rates of captured immunization opportunities for adolescent office visits (Supplemental Fig 4). The EHR-based alerts offered suggestions but required no action or documentation on the part of the clinician.…”
Section: Clinician-focused Interventionmentioning
confidence: 99%
“…21,22 Recognition of these obstacles triggered calls to develop innovative systems to foster adolescent vaccine delivery. 5,23 Research in this area is warranted since interventions using electronic health record (EHR)-based, clinician-focused decision support (CDS) to support early childhood and influenza vaccination have had mixed results, 24,25 and no published studies of EHR-based alerts have addressed adolescent vaccination. In addition, although basic reminder calls to families have proven effective in fostering vaccination, 26 only 2 studies of reminder calls for adolescent vaccination have been published, revealing mixed results.…”
mentioning
confidence: 99%
“…Research has shown that EHRs, properly deployed for immunization decision support, demonstrate the clearest benefit to the quality of child health care. [43][44][45] The rules for what immunizations should be delivered when and under what clinical circumstances can be embedded in an EHR, but most pediatricians report that their EHR system lacks this function. 46 …”
Section: Immunization Decision Supportmentioning
confidence: 99%